Design Optimization of CMOS- MEMS Staggered Vertical Comb Based Micro Scanners - Wenhao Chen; Mingzheng Duani; Hadi Tavakkoli; Huahuang Luo; Bin Zhao; Wibool Piyawattanametha; Yi-Kuen Lee (2022 IEEE Sensors, 2022)
For the first time, we propose a novel CMOS-MEMS staggered vertical comb based micro scanner (SVC-MS) for ID static out-of-plane rotation using CanSemiconductor 0.18μm IP6M, TSMC CMOS foundry process. Based on compact model, the parametric analysis shows the torsion spring width and the actuator thickness are two critical parameters in term of design, and design optimization using dimensional analysis can be conducted for improving the rotation angle(Ooptical=19.26°) and figure of merit (FoM=O.6) by 400% and 150% compared with the first design. The optimized design shows miniaturization with a mirror size of 800μm and a higher FoM of 0.6 among previous designs. In addition, critical ratio of geometry for increasing the input-output response with a lower voltage is found, which can improve the actuator's performance.
Keywords: Advanced MEMS and NEMS Technologies; Advanced Surface Polishing Techniques; Advanced Fiber Optic Sensors